Contextualisation of closed-loop supply chains for sustainable development in the Chinese metal iIndustry - Huang, Juanling (2009)
There are many factors influencing the sustainability of Closed-Loop Supply Chain (CLSC), in terms of industrial operation flows and environmental perspectives. This research aims to identify these factors in order to provide a better understanding of the process flows and interactions between the primary and secondary metal manufacturers and remanufacturers. In particular, it focuses on the influences of the Customer, Environment and Technology (CET) factors, with the intention of finding out “the specific approaches and techniques the Chinese metal manufacturers and remanufacturers adopt for sustainable development of the CLSC”. Qualitative case studies were performed in seven companies in the Pearl River Delta (PRD) region of South China. These companies are Small and Medium Enterprises (SMEs) of primary metal manufacturers, secondary metal remanufacturers, dismantlers, and third party reverse logistics providers. Data and information were collected through semi-structured interviews and observations on sites, in order to analyse the process flows in the supply chains. The key findings include the demonstration of the CLSC networks in the context of the Chinese metal industry, and the development of the process maps and Positioning Tool for case companies to identify themselves in the CLSC. These are theoretical and practical supports for academics and companies to understand the handling of various qualities and quantities of primary and secondary metals. Simultaneously, they assist companies in identifying and positioning themselves in the CLSC in order to define their direction for sustainable development in the long-term.